Modeling pseudo-elasticity in small-scale ThCr2Si2-type crystals - Bakst, Ian N.; Weinberger, Christopher R.; Lee, Seok-Woo; Sypek, John T.; Neilson, James R. (Colorado State University. Libraries, 2018)
Crystals of the ThCr2Si2-type structure comprise a large class of known compounds, and observations of superconductivity in some of the compounds generated significant interest in these materials. Recently, nano-indentation experiments have shown that at room temperature, small-scale crystals of CaFe2As2 exhibit pseudo-elastic behavior with recoverable strains of over 10%. These experiments also demonstrate the potential for shape memory effects at cryogenic temperatures, behavior which has previously been related to its magnetic phase transitions. In this work, the phase transitions of CaFe2As2 are investigated using density functional theory (DFT) in conjunction with analytical models. The models demonstrate that both uniaxial and hydrostatic loading can give rise to pseudo-elastic behavior. These models are then applied to LaRu2P2, which does not exhibit a magnetic phase change, but is still found to have a similar pseudo-elastic response. A suite of parameters useful in quantifying the complex responses of these compounds is presented and it is demonstrated that c-axis strain is the critical loading parameter in predicting the pseudo-elastic behavior. These results provide a method of connecting local chemical tuning to macroscopic behavior.
These data files contain the raw DFT data of the compression of CaFe2As2 and LaRu2P2 unit cells used for the construction of the composite model. The output of the model is also included in this data set.
Keywords: pseudo-elastic; superelastic; phase-change; LaRu2P2; CaFe2As2; 122-type superconductors; DFT